2022
DOI: 10.1186/s12889-022-13481-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, characteristics, and psychological outcomes of workplace cyberbullying during the COVID-19 pandemic in Japan: a cross-sectional online survey

Abstract: Background The rapid introduction of teleworking due to the coronavirus disease 2019 pandemic has led to concerns about increases in cyberbullying (CB) worldwide. However, little is known about workplace CB in non-Western countries. The first objective was to clarify the prevalence and characteristics regarding workplace CB victimization in Japan. The second objective was to demonstrate the psychological outcomes of CB victimization in combination with traditional bullying (TB). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 94 publications
1
18
0
Order By: Relevance
“…Enduring Factors: Personal Characteristics Demographic factors. Younger age was found to be a consistent risk factor for cyberbullying across eight studies (Ikeda et al, 2022;Jain et al, 2020;Lee et al, 2022;Teng et al, 2021;Trompeter et al, 2022;Wang et al, 2022;Yang, 2021;. Of note, one study pointed out that the age group of 17-18 was highly susceptible to cyberbullying victimization (Jain et al, 2020).…”
Section: Enduring Factors: Cultural Factor and Individual Consciousnessmentioning
confidence: 96%
See 2 more Smart Citations
“…Enduring Factors: Personal Characteristics Demographic factors. Younger age was found to be a consistent risk factor for cyberbullying across eight studies (Ikeda et al, 2022;Jain et al, 2020;Lee et al, 2022;Teng et al, 2021;Trompeter et al, 2022;Wang et al, 2022;Yang, 2021;. Of note, one study pointed out that the age group of 17-18 was highly susceptible to cyberbullying victimization (Jain et al, 2020).…”
Section: Enduring Factors: Cultural Factor and Individual Consciousnessmentioning
confidence: 96%
“…Routine online activities were consistently found to contribute to cyberbullying victimization and perpetration. Internet addition and more online activities such as chatting, gambling, and playing games were found to be associated with cyberbullying perpetration in three studies (Kee et al, 2022;Maftei et al, 2022;Vejmelka & Matković, 2021) and were found to be associated with cyberbullying victimization during the pandemic in five studies (Ikeda et al, 2022;Jain et al, 2020;Morales-Arjona et al, 2022;Paek et al, 2021;Vejmelka & Matković, 2021). Additionally, two studies examined COVID-19 information overload and active information dissemination as factors associated with cyberbullying perpetration (Wang et al, 2022) and cyberbullying victimization (Ikeda et al, 2022), respectively.…”
Section: Transient Factors: Covid-19-related Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…These plans make it possible to carry out a sociological study of the student body to detect at an earlier stage any type of hostile situation among students [ 13 ], as well as the possible conditioning factors that may predispose a person to being a victim, such as unpopularity, shyness, educational needs, ethnicity or sexual orientation. Likewise, it would be observed whether a student could be a possible aggressor or have a role as a “student mediator” who would help the victim by informing teachers about any conflict inside or outside the classroom [ 1 , 2 , 14 ]. There are several methods to control bullying, which are chosen by schools according to their preferences and needs.…”
Section: Introductionmentioning
confidence: 99%
“…3 In Japan, the frequency of workplace bullying has been reported to be relatively low compared with other countries, with published estimates ranging from 9.0% to 9.7%. 4,5 Workplace mistreatment creates cost problems due to increased absenteeism, presenteeism, and turnover. 6 Individuals who experience mistreatment also take more sick leave.…”
mentioning
confidence: 99%